Investigating and mitigating errors in the remote sensing of maritime low clouds at night - Turner, Jesse, author; Miller, Steven D., advisor; Kummerow, Christian D., committee member; Smith, Ryan G., committee member; Noh, Yoo-Jeong, committee member (Colorado State University. Libraries, 2024)
Low clouds are ubiquitous to the world's oceans, affecting aviation, maritime transportation, and the structure and dynamics of the broader atmospheric system. Understanding the diurnal properties and distributions of these clouds requires an observing system capable of spanning vast regions of ocean devoid of surface-based observations. Here, earth observation satellite imagery provides potentially valuable information on cloud coverage over the oceans. The brightness temperature difference (BTD) between the longwave infrared (e.g., 11 µm) and shortwave infrared (e.g., 3.9 µm) window band measurements is commonly used as a first-order bi-spectral test to identify low clouds over the ocean at night. Occasionally, unusual patterns of clear-sky features in this BTD occur, giving rise to spurious false-positive cloud measurements. These confusing signals are caused by nuances of the atmospheric and surface emission sensitivity at these two wavelengths. Ideally, positive values in the 11 µm - 3.9 µm BTD are caused by actual low clouds, owing to slightly higher emissivity at the longwave IR compared to the shortwave IR. However, a clear-sky environmental scenario can mimic this signal: a warm and moist air mass over a cold region of water. These same environmental conditions are conducive to advection fog formation, compounding the interpretation of conventional infrared-based cloud detection in these regions. Moonlight reflectance, when available from the Day/Night Band on the Visible/Infrared Imaging Radiometer Suite (VIIRS), can help to disentangle cases of actual vs. false low cloud (FLC). This research examines cases from the United States east coast, the Mexico south coast, and the large-scale Gulf Stream to investigate the physical causes of false cloud signals. Insight gained from this research can help forecasters and researchers determine which physical regions are prone to false alarms, and in complement, which regions offer higher confidence for cloud detection. Further, this study uses numerical model data and radiative transfer simulations to estimate the positive signals caused solely by air mass over cold water effects. This simulation method lends insight on the global extent and frequency of nighttime maritime low cloud overstatement. Knowledge of the patterns of false signals in the IR BTD provides opportunities to improve products that depend on the nighttime low cloud test, such as fog and visibility warnings, sea-surface temperature cloud masking, and cloud climatologies used for climate research. The simulation also provides a novel predictive tool for anticipating potential regions of both false alarm low cloud and regions prone to advection fog formation.